Female university students in blesser-blessee relationships : toward a social and behavioural change communication strategy - Nukeri, Ntsentselelo Delvah (My University, 2024)
The purpose of this study was to explore the experiences of female university students in blesser-blessee relationships and to develop a communication strategy that can be used to educate young girls towards a behavioural change that may contribute to combating transactional relationships. Qualitative, applied, and interpretivist research was conducted to explore the benefits and challenges of blesser-blessee relationships, and the broader experiences of female university students in blesser-blessee relationships in the Limpopo Province. Thus, 15 undergraduate and postgraduate female university students and three health practitioners who worked directly with female students participated in this study. This study used in-depth interviews to collect data. The study drew largely from the Health Belief Model coined by Becker (1974) and the Typology of Interpersonal Sugar Relationships Theory coined by Scull (2019). The study highlights the hidden dynamics of blesser-blessee relationships. The findings revealed that female university students in this study do not engage in blesser-blessee relationships due to poverty, but largely because of their placement of self-identity, happiness, and beauty on the possession of expensive materials. The pursuit of materialism tends to be an influencing factor for young females to be involved in this sort of transactional relationship. Moreover, they are influenced by their family members to pursue a man who is economically stable and able to provide for the family. Blesser-blessee relationships were found embedded with dire health consequences; hence, this study developed a behavioural change communication strategy and a campaign that could be used to educate young girls against this phenomenon.
Thesis (M. A. (Communication Studies)) -- University of Limpopo, 2024
Keywords: Transactional relationships; Materialism; Mavuso; Blessee; Blesser; Materialism; Girls; College students -- South Africa -- Limpopo; Social change; Behavior; Communication -- Social aspects -- South Africa -- Limpopo